980 Readmissions Within 30 Days of Discharge Following Single Stoma Formation. (19th August 2022) - Plonkowski, A; Allison, C; Philipson, P; Brady, R
Abstract: Background: Patients who have stoma surgery are at higher risk for readmission following discharge. Some may benefit from closer post-discharge surveillance to detect complications earlier and provide timely treatment to avoid readmission. However, there are a paucity of contemporary tools to identify those at higher risk of readmission following discharge after stoma surgery. Here, we aimed to determine factors associated with readmissions, within 30 days of discharge, following stoma surgery. Method: Retrospective review of all patients who underwent a single stoma formation at a single tertiary colorectal service (2019–2021). Results: 423 patients underwent 220 ileostomy and 203 colostomy formation surgeries. Overall, 87 (20.6%) patients were readmitted within 30 days of discharge. The rate of readmission in those with IBD (n=87) was 18.4%, cancer (n=208) 20.7%, diverticular disease (n=45) 17.8% and vascular disease (n=19) was 36.8% (p>0.05). There was no association between readmission and gender, aetiology, smoking, weight, or discharge to social care. The only comorbidity associated with increased readmission was chronic heart failure (p=0.05), no other comorbidities were associated with increased readmission. There was an increased incidence of readmission in patients with post-operative stoma-specific complications (bleeding p=0.02; high-output stoma p=0.01) and in patients who received loop ileostomies compared to other stoma types (34.0% versus 18.6%; p=0.01). There was a protective effect in those given nutritional supplements post-operatively (p=0.04). Conclusion: Readmission following single stoma formation is related to variables that potentially provide the means to triage, risk score and potentially predict readmission. Further work is being undertaken to develop and prospectively to validate a model.